Conditioning‐based outcomes after allogeneic transplantation for myeloma following a prior autologous transplant (1991‐2012) on behalf of EBMT CMWP. (25th December 2019) - Hayden, Patrick J.; Iacobelli, Simona; Pérez‐Simón, José Antonio; van Biezen, Anja; Minnema, Monique; Niittyvuopio, Riitta; Schönland, Stefan; Meijer, Ellen; Blaise, Didier; Milpied, Noel; Márquez‐Malaver, Francisco J.; Veelken, Joan Hendrik; et al.
Abstract: Objectives: The aim of this study was to compare the effect of the intensity of conditioning approaches used in allogeneic transplantation in myeloma—reduced intensity conditioning (RIC), non‐myeloablative (NMA), myeloablative conditioning (MAC) or Auto‐AlloHCT—on outcomes in patients who had had a prior autologous transplant. Methods: A retrospective analysis of the EBMT database (1991‐2012) was performed. Results: A total of 344 patients aged between 40 and 60 years at the time of alloHCT were identified: 169 RIC, 69 NMA, 65 MAC and 41 Auto‐Allo transplants. At a median follow‐up of 54 months, the probabilities of overall survival (OS) at 5 years were 39% (95% CI 31%‐47%), 45% (95% CI 32%‐57%), 19% (95% CI 6%‐32%) and 34% (95% CI 17%‐51%), respectively. Status at allogeneic HCT other than CR or PR conferred a 70% higher risk of death and a 40% higher risk of relapse. OS was markedly lower in the MAC group ( P = .004). MAC alloHCT was associated with a higher risk of death than RIC alloHCT until 2002 (HR = 4.1, P < .001) but not after 2002 (HR = 1.2, P = .276). Conclusion: From 1991 to 2002, MAC was associated with poorer OS. Between 2003 and 2012, there were no significant differences in outcomes based on these different approaches.